Prospects and Challenges of Green Buildings and Green Affordable Homes-Concept: A Study with Reference to Ernakulam, Kerala - Manoj P K (GRA - GLOBAL RESEARCH ANALYSIS, 2013)
The concept of ‘Green Affordable Homes’ has assumed tremendous significance in the contemporary centrality because of the utmost importance of environment-friendly development initiatives, not only in the construction and housing development arena alone but in the entire gamut of all types of human endeavors as well. The need for preserving energy and ensuring high energy efficiency has added another dimension to the significance of green and affordable homes. As the governments the world over are keen on promoting various environment-friendly and energy-saving development initiatives, ‘Green Buildings’ in general and ‘Green Homes’ in particular are growingly becoming the preferred development models of governments, and also financing agencies, regulatory authorities, developers etc. In this context, this paper makes an overall review of the vital significance of green, affordable and energy-efficient construction activities, makes an empirical study of the awareness level, attitudinal issues, problems and prospects of such houses, and makes some suggestions based on the findings of the study.